EFEK EKSTRAK BAWANG MERAH ( Allium ascalonicum L.) TERHADAP PERUBAHAN SUHU TUBUH PADA TIKUS PUTIH (Rattus norvegicus) YANG MENGALAMI DEMAM - I Gede Agus Wiryawan (Coping: Community of Publishing in Nursing, 2015)
Red onion is one of multipurpose herb. Onion bulbs contain nutrients and non-nutritional substances (phytochemicals). Phytochemical compounds found in onion one is flavonoids. Flavonoid compounds has been known that have anti-inflammatory effects and has also worked as an antipyretic effects of inhibitors of cyclooxygenase (COX), which Has function to trigger the formation of prostaglandins. Prostaglandins play a role in the inflammatory process and increased body temperature. When prostaglandins are not inhibited, the body temperature increases that would result in fever. This study aimed to determine the effect of onion extract (Allium ascalonicum L.) towards the changes in body temperature in white rats   (Rattus norvegicus) who experience fevers. This research is true experimental research with pretest and posttest with control group design. Twenty-eight white male rats aged 2-4 months is induced by DPT vaccine (0.5 cc intraperitoneal), and then divided into 4 groups. Group I (onion extract dose 126mg/100 g BB), group II (onion extract dose 252mg/100gr BB), group III (onion extract dose 378mg/100 g BB), group IV (distilled water) as a negative control. Temperature measurements carried out at the first before induction, 1 hour after induction and every 30 minutes until 120 minutes after treatment. Results were analyzed by ANOVA test followed by post hoc test. The conclusion of this study is that there is the effect of extracts of onion (Allium ascalonicum L.) to changes in body temperature of rats (Rattus norvegicus) with fever